A real-time image dynamic range compensation for scanning electron microscope imaging system - Sim, , KS; Kamel, , NS; Chuah, , HT (2005)
This paper presents the development and implementation of a real-time dynamic range compensation system for scanning electron microscope (SEM) imaging applications. Compared with conventional automatic brightness contrast compensators that are based on the average image or pixel intensity level, the proposed system utilizes histogram-profiling techniques to compensate continuously the dynamic range of the processed video signal. The algorithms are implemented in software with a frame grabber card forming the front-end video capture element. The proposed technique yields better image compensation compared with conventional methods.